Firm-specific capital, inflation persistence and the sources of business cycles - Madeira, J. (European Economic Review, 2015)
This paper estimates a firm-specific capital DSGE model. Firm-specific capital improves the fit of DSGE models to the data (as shown by a large increase in the value of the log marginal likelihood). This results from a lower implied estimate of the NKPC slope for a given degree of price stickiness. Firm-specific capital leads to a better fit to the volatilities of macro variables and a greater persistence of inflation. It is also shown that firm-specific capital reduces the dependence of New Keynesian models on price markup shocks and that it increases the persistence of output to monetary shocks.